1992
DOI: 10.1063/1.350590
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a deep level in p-type Hg0.78Cd0.22Te with high dislocation density

Abstract: To investigate the possibility that deep levels are associated with dislocations in narrow band gap HgCdTe, deep level transient spectroscopy has been used to study n+-p diodes fabricated on p-type bulk Hg0.78Cd0.22Te samples with either a ‘‘normal’’ dislocation density of about 105 cm−2 or a high dislocation density of about 106 cm−2. These samples which are gold doped with a hole concentration of 1.2×1015 cm−3, have a band gap of about 0.12 eV at 77 K. In samples with a ‘‘normal’’ dislocation density, a deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…To determine more precisely the position E °, we need to know exactly the density of electrically active dislocations. However, our results agree with a mid-gap level found in p-Hg0.78Cd0.22Te having a high dislocation density [4] and also with the increase in donor concentration associated with the formation of dislocations observed in [2]. Lastly, note also that a possible model for the interaction mechanism between point defects and the moving dislocations has been proposed recently in InP [11].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…To determine more precisely the position E °, we need to know exactly the density of electrically active dislocations. However, our results agree with a mid-gap level found in p-Hg0.78Cd0.22Te having a high dislocation density [4] and also with the increase in donor concentration associated with the formation of dislocations observed in [2]. Lastly, note also that a possible model for the interaction mechanism between point defects and the moving dislocations has been proposed recently in InP [11].…”
supporting
confidence: 92%
“…Recent investigations [1][2][3] have demonstrated that dislocations originating from material growth or array processing have a dramatic effect on the overall performance of devices. Note also that a deep level located at about 60 meV above the valence band has been evidenced by deep level transient spectroscopy measurements in p-Hg0.78Cd0.22Te having a high dislocation density [4]. In this letter we report on some of our investigations of the electrical properties of n-type Hg0.sCd0.2Te plastically deformed.…”
mentioning
confidence: 70%
“…Such estimation should be valid not only for the abrupt junction. Note, that in paper [11] investigating a similar material with x 0X215 by the DLTS method the trap levels with the same energies were found: hole trap with E t1 E v 0.035 eV and electron trap with E t2 E v 0.043 eV at T $ 25 to 30 K. The authors [12] observed the level of E t3 E v 0.062 eV in samples with a large amount of dislocations.…”
Section: Experiments and Discussionmentioning
confidence: 67%
“…3). In papers [9][10][11] Figure 2 shows I-V and dI/dV-V characteristics of the investigated diode after applying the pressure. A pressure of less than 2 Â 10 7 N/m 2 practically does not affect the diode characteristics.…”
Section: Experimental and Discussionmentioning
confidence: 99%